Study of MIMO techniques for Power Line Communications. - Corchado-López, Julio A. (UMA Editorial, 2024)
Power line communication (PLC) consists in the exchange of information over electrical cables. PLC takes advantage of the ubiquity of already deployed power delivery networks and provides access to telecommunication services without any further infrastructure installation. Traditionally, PLC systems used only two conductors, thus resulting in a single input single-output (SISO) system. However, most indoor power lines are composed of three conductors, and this third conductor can be exploited to enable a multiple-input multiple-output (MIMO) system over this channel. Exploitation of MIMO capabilities enhance the achievable performance over a given medium. MIMO features have been extensively studied for wireless environments but MIMO in wired scenarios show some distinct aspects with respect to their wireless counterparts. The first contribution of this work is a multiconductor transmission line (MTL)-based MIMO PLC model which captures spatial correlation in a way that other MTL-based models cannot. Three topological modifications on the channel model are proposed to achieve this. The proposed model leads to MIMO channels similar to measured ones, both in terms of SISO (attenuation) and MIMO (spatial correlation) features. The second contribution shows, by means of measurements, that spatial correlation in PLC channel responses does not display a significant dependence with respect to frequency and that there exist alternative injection modes to the usual differential mode which yield lower spatially correlated MIMO channels.
Lastly, the third contribution provides a characterization of the noise correlation in MIMO PLC in the 2-108 MHz band, showing that noise in the frequency modulation (FM) band displays very high spatial correlation. It has been proven that the exploitation of the aforesaid correlation, by means of a linear precoding system with a whitening transformation, makes PLC feasible in the FM band with an injected power spectral density (PSD) as low as -100 dBm/Hz.
Keywords: Telecomunicaciones - Tesis doctorales; Control automático - Tesis doctorales; MIMO; PLC